(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The barrier discharge plasma (BDP) modification represents an appropriate method for the polarity increasing of the wood surfaces. The surface properties of various wood species (beech, maple, birch) were pre-treated using BDP at atmospheric pressure in air were evaluated by contact angle measurements. The FTIR spectrum of the three tested species of wood is a mixed spectrum (composition) of cellulose and lignin with characteristic peaks corresponding to –OH bonds (with a maximum at about 3400 cm-1 ) and fingerprints assigned to the –CO, –COO and –CH2– bonds typical for polysaccharides.